SALAFI-INFLUENCERS ON SOCIAL MEDIA: ANALYTICAL STUDY OF OF THE DISCOURSE OF NEO-SALAFI PREACHERS - Abdulmajid, Adib (UIN Sunan Kalijaga Yogyakarta, 2023)
This discourse analytical study tackles the rise of Neo-Salafism in the digital age. It constitutes an exploration of the discursive technics, strategies and practices employed by the new generation of Salafī preachers on social media. It strives to unveil the various discursive methods of indoctrination pursued by Salafi-influencers and the ends such strategies tend to serve. It involves an exploration of linguistic and contextual activities and seeks to identify explicit and implicit messages incorporated into the discourse of those young preachers. The main hypothesis upon which this study rests is that young preachers of Neo-Salafism resort to modified discursive technics that correspond to the age of digitalization and social media activism for the sake of ensuring a resounding impact among their addressees. These recipients represent a social incubator to the extremist Salafī ideology and a potential pool for a new wave of radicalization among the Muslim youth worldwide. A multi-dimensional methodological framework is employed to tackle the topic raised by this study. The data analyzed within the framework of this study consist of speeches and instructional communications by young Salafī preachers published through different social media platforms. Salafi-influencers seem to have developed a discourse characterized by certain manipulative strategies to communicate particular ideological messages and to indoctrinate recipients.